Visualising the Intended Practical Doing: Future-Oriented Movements in Swedish Vocational School Workshop Settings - Stig-Börje Asplund; Nina Kilbrink; Hamid Asghari (European Research Network Vocational Education and Training (VETNET), 2021)
Context: This article focus on teaching and learning processes in a vocational classroom in Swedish vocational education. There are few studies within the field of vocational education that have a focus on how vocational learning is done in interaction in the vocational classroom/workshop, and what vocational learning content is displayed in the interaction between teacher and student, and thus made possible to learn. This article aims to fill this gap by exploring the future-oriented movements that take shape when a vocational teacher and vocational students negotiate how a practical task could, and should, be handled and solved in vocational teaching situations in vocational plumbing school workshop settings. An increased understanding of these processes can help to improve the actual teaching of a specific subject content to support students in their vocational learning, aiming for learning a professional trade. Methods: The data consists of video recorded lessons from the Sanitary, Heating and Property Maintenance Programme in Swedish upper secondary school. Through concrete empirical examples from video recorded lessons the article explores the interaction between teachers and students in vocational school workshop settings using CAVTA. CAVTA is based on Conversation Analysis (CA) and Variation Theory (VT) and is a theoretical and methodological framework that can be used together and integrated to reach understanding of both how- and what-aspects of the learning process in practice, when analysing teaching and interaction. Findings: Findings shows how aspects concerning a specific vocational learning content that revolves around a vocational practical doing compete for the space with a vocational learning content of a more general nature. These general objects of learning are also related to work-specific vocational learning and knowledge in relation to the future profession, but on a more general level than the task specific vocational knowledge. Altogether, this illuminates how different layers of work-specific vocational learning are made visible in the interaction, and how they mutually contextualise each other in the here and now. Conclusion: This article illustrates that the specific and the general vocational learning content can complement each other and open up for a more in-depth vocational learning. In conclusion, this article emphasises the importance for vocational teachers to develop teaching strategies to navigate between helping the students in their problem solving here and now, and contextualising the specific vocational learning content and making vocational learning relevant for future vocational occupation and working life.